PEMANFAATAN VIRTUAL REALITY TERHADAP MINAT BELAJAR SISWA SD - Ayumi Suci; Lili Kasmini; Anggi Susilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning interest of elementary school students, which is indicated by a lack of attention, interest, involvement, and feelings of enjoyment in learning that still uses conventional media. The problem formulation in this study is how the use of Virtual Reality (VR) in the form of 360° videos on the learning interest of elementary school students. This study aims to describe the use of VR in increasing the learning interest of third-grade students in science learning. The study used a qualitative approach with a descriptive type, with 28 research subjects at SD Negeri 22 Banda Aceh. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions with validity tests using triangulation. The results showed that before the use of VR, students' learning interest was at a score of 1-2 with a category of sufficient to less (assessment using a scale of 1 to 4, ranging from